Nio Modification Using Zr4+ And Ca2+ For Dielectric Improvement - Syed Salim, Sharifah Aishah (2013)
In this research, the effect of Zirconium ions (Zr4+) and Calcium ions (Ca2+) dopant on NiO was investigated. The electroceramic of Ni(1-x)ZrxO, Ni(1-x)CaxO and Ni0.95Zr0.02Ca0.01 was prepared by using solid state reaction method. Three main raw materials of NiO, ZrO2 and CaO were mixed for 24 hours, then were calcined at 1000ºC. Ni(1-x)ZrxO and Ni(1-x)CaxO was sintered at 1280°C for 10 hours and 1250°C for 4 hours, respectively. Ni0.95Zr0.02Ca0.01 was sintered at 1200ºC, 1250ºC and 1300ºC for 5 hours. The 1250ºC for 5 hours was identified as optimum sintering profile for Ni0.95Zr0.02Ca0.01 formation. XRD analysis on sintered sample showed the single phase formation of Ni(1-x)ZrxO, Ni(1-x)CaxO and Ni0.95Zr0.02Ca0.01. FESEM observation on the Ni(1-x)ZrxO showed that grain size are bigger with increasing amount of dopant and Ni(1-x)CaxO shows that grain size are getting larger with increasing amount of dopant. Meanwhile the grain size of Ni0.95Zr0.02Ca0.01 are larger with the increasing sintering temperature. The densification of Ni(1-x)ZrxO, Ni(1-x)CaxO and Ni0.95Zr0.02Ca0.01 was improved using Zr4+ and Ca2+ doping and the porosity decrease at higher dopant concentration. The dielectric behavior of Ni(1-x)ZrxO with x = 0.02 mole % Zr4+ exhibited highest dielectric constant (700) with moderate dielectric loss (0.16). Meanwhile, the dielectric behavior of Ni(1-x)CaxO samples show that the sample doped with x = 0.01 mole % Ca2+ obtained the lowest dielectric loss (0.05) but moderate in dielectric constant (123), measured at 1 MHz. The combination of this two optimum dopant content, Zr4+ = 0.02 mole % and xix Ca2+ = 0.01 mole %, has been applied to produce Ni0.95Zr0.02Ca0.01. The dielectric behavior of Ni0.95Zr0.02Ca0.01 posses the highest dielectric constant (727) and lowest dielectric loss (0.04).